PELATIHAN PEMBUATAN PUPUK BOKASI UNTUK MENDUKUNG PERTANIAN ORGANIK DI SMKN 1 WONOSARI MALANG - Nur Kusmiyati; Ulfah Utami; Prilya Dewi Fitriasari; Muhammad Asmuni Hasyim; Fitriyah Fitriyah; Azizatur Rahmah (LPPM Universitas Bina Bangsa, 2022)
Community service activities regarding training in making bokasi fertilizers were carried out at SMKN 1 Wonosari Malang to be carried out to support organic farming. The purpose of this service activity is to provide knowledge about making bokasi fertilizers in supporting organic farming efforts. These service activities are carried out using several methods consisting of outreach; demonstrations and practices; guidance followed by mentoring; as well as an analysis of the evaluation of the service program. This training was attended by 30 participants consisting of class XII students at SMKN 1 Wonosari, Malang Regency. Based on the results of the questionnaire data analysis, it can be seen that the knowledge of the participants about bokasi fertilizers in an effort to support organic farming has increased, after participating in training activities; participants are able to make bokasi fertilizer; there is a change in the pattern of knowledge related to bokasi fertilizer so that participants can plan to produce bokasi fertilizer. Overall, it can be said that the training program for making bocation fertilizer in an effort to support organic farming is running effectively and is able to change the knowledge and abilities of students at SMKN 1 Wonosari, Malang Regency